Analyzing Teachers’ Perception on the Implementation of the Assessment Process in Merdeka Curriculum - Teguh Satria Amin; M Meisuri; Zulfitri; Nurlaili; Yulia Sari Harahap (International Journal of Educational Research Excellence (IJERE), 2023)
This study aims to describe the teachers’ perception on the implementation of the assessment process in Merdeka curriculum. A qualitative approach was used to analyze data of the study. This research was conducted in nine teachers that following PPG Dalam Jabatan Gelombang II 2023 in Universitas Muslim Nusantara Al Washliyah. In the data analysis, a detailed description of teachers’ perceptions was analyzed. The data obtained from interviews were transcribed and then interpreted. The transcription of the interview and observation were coded into categories. Then the categorized data was argumentatively analyzed and described. The results of data analysis showed that teachers prepared teaching module to implementing the teaching and learning processes in the classroom. The teaching module consist of the assessment for Diagnostic Cognitive and Diagnostic NonCognitive, Project-based assessments, Performance assessments, Formative assessments, Summative assessments after the students have finished their learning. The collected data are examined through the application of descriptive statistical methods. The knowledge, attitudes, and abilities that students acquire during learning activities determine their learning outcomes. A school report based on the Merdeka Curriculum school report application presents the students’ learning outcomes. As a result, most teachers are aware of the Merdeka Curriculum's assessment requirements and have completed them.